Increased risk of peptic ulcer following periodontitis: a systematic review and meta-analysis - Amir Motaghi; Mojtaba Bayani; Hamid Mehrafarid; Fatemeh Abdolalian; Amir Almasi-Hashiani (European Journal of Medical Research)
Abstract Background Considering the importance of periodontal diseases in the occurrence of systemic diseases such as peptic ulcer diseases, the relationship between peptic ulcer diseases and periodontal diseases is important, therefore, the purpose of this meta-analysis is to investigate the relationship between peptic ulcer and periodontitis. Methods In this systematic review, to find the relevant articles, PubMed, Web of Science and Scopus databases were reviewed according to the search strategy. All studies were screened and eligible studies were selected to include in the meta-analysis. The quality of the selected articles was evaluated by the Newcastle–Ottawa assessment scale. I-square statistic was used to investigate the heterogeneity between studies and its significance was checked with Chi-square test. In cases where there was serious heterogeneity, random-effects model was used for data synthesis, otherwise fixed-effects model was used. Results Five studies from different countries were included, among which there were two cross-sectional, two case–control, and one cohort study. Based on the primary studies that reported the adjusted results to control for confounders, a significant relationship between periodontitis and peptic ulcer was observed (effect size (ES) = 1.47, 95% CI 1.01–1.93, I-square = 93.1%), and similar significant results were also obtained regarding the relationship between periodontitis and duodenal ulcer (ES = 1.10, 95% CI 1.02–1.17, I-square = 33.0%), but there is no significant relationship between periodontitis and gastric ulcer (ES: 1.33, 95% CI 0.71–1.96, I-square = 74.0%). Conclusion The results of this study showed that periodontitis is associated with increased risk of peptic ulcer and duodenal ulcer, but no significant relationship was observed with gastric ulcer. Therefore, the implementation of periodontitis treatment protocol can increase the success of peptic ulcer and duodenal ulcer treatment.